HEAT RECUPERATION - S. L. Rovin; L. E. Rovin; A. V. Tkachenko (Литьë и металлургия)
Heat recovery is an effective method of shortening specific energy consumption. new constructions of recuperators for heating and cupola furnaces have been designed and successfully introduced. two-stage recuperator with computer control providing blast heating up to 600 °C and reducing fuel consumption by 30% is of special interest.